An Impact Evaluation of a Newly Developed Pediatric Cardiac Intensive Care Unit. Issue 1 (January 2015) - Welander, Michelle Hanna; Keller, Sheila D.; Northington, LaDonna
Abstract : Purpose: The highly complex pediatric patients with congenital heart disease require interprofessional teamwork and collaboration to ensure high-quality outcomes with low mortality and morbidity ( Congenit Heart Dis . 2013;8:3–19). The purpose of this study was to conduct an impact evaluation for a newly formed pediatric cardiac intensive care unit (PCICU) and to answer: Is there a difference between the pediatric intensive care unit and the PCICU on clinical outcome measures of pediatric cardiac postoperative patients and nursing resources? Design: A retrospective pretest/posttest design was used with the independent variables being type of intensive care unit. The confounding variables included demographic data, clinical outcome data, registered nurse (RN) staffing data, and RN turnover data. Setting: The setting was a large, level I pediatric medical and surgical intensive care unit (ICU) located at a children's hospital within an academic medical center. Sample: The population was pediatric cardiac postoperative patients. Patients excluded were those older than 18 years or cases without a Society of Thoracic Surgeons and European Association for Cardiothoracic Surgery Congenital Heart Surgery Mortality Category score of 1 through 5. Methods: Owen's impact evaluation method and descriptive statistical measures, t test and Pearson χ 2 test, were used for analysis. Results: Demographic data were comparable between the pediatric intensive care unit (n = 296) and PCICU (n = 333). No statistical differences were found in several of the clinical outcome measures. Statistically significant differences were found in surgeon ( P = .00) and RN nursing hours per patient day for all cardiac patients ( P = .01). The PCICU time frame had a higher RN turnover rate. Conclusions: The majority of quality measures were not statistically different between the 2 ICUs. Even though statistical significance was not reached, the clinical impact of the PCICU's reduction in patient infections, mortality, and ICU length of stay was noted. Implications: This evaluation has provided organizational leaders the quality indicators and costs that have been impacted with the addition of interprofessional teamwork and coordination of care through the development of a PCICU.